2017
DOI: 10.1007/s00266-017-0843-x
|View full text |Cite
|
Sign up to set email alerts
|

Giant Rhinophyma: A Rare Case of Total Nasal Obstruction and Restitutio Ad Integrum

Abstract: Rhinophyma is considered the end stage in the development of rosacea, accompanied by hypertrophy of the sebaceous glands, which causes an enlargement of the nose. It is an uncommon condition that often results in both functional and cosmetic impairment. A large variety of surgical and nonsurgical treatments have been published to treat it. Closure is usually obtained by wound granulating in by secondary intention, skin grafting or local flaps. Rarely these lesions can attain a giant size and pose a challenge i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 24 publications
0
6
0
Order By: Relevance
“…18 Additionally, 3 case studies discussing treatment of severe rhinophyma with electrocautery reported re-epithelialization times between 2 and 4 weeks. 19,20,31 All studies reported good hemostasis and the added benefits of short surgical times and cost-effectiveness. 16 18,20,21…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…18 Additionally, 3 case studies discussing treatment of severe rhinophyma with electrocautery reported re-epithelialization times between 2 and 4 weeks. 19,20,31 All studies reported good hemostasis and the added benefits of short surgical times and cost-effectiveness. 16 18,20,21…”
Section: Discussionmentioning
confidence: 99%
“…They discuss the ability to preserve the alar cartilage and deep pilosebaceous tissue with the use of electrocautery, which allows for recreation of the aesthetic subunits of the nose. 31 However, due to the intense heat generated during excision with electrocautery, there is an added risk of damage to the underlying cartilaginous structure, potentially prolonging scarring or necrosis. 32,33…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Rhinophyma is a rare and painless benign tumor of the skin of the nose characterized by hyperplasia of the sebaceous glands, connective tissue, and blood vessels [1]. Rhinophyma is generally confined to the lower nose and does not involve the bone or cartilage framework.…”
Section: Introductionmentioning
confidence: 99%
“…Rhinophyma is a rare, disfiguring disease characterized by a progressive hypertrophy of the soft-tissues of the nose with its increased volume, mainly in the lower half, and often associated to an end-stage of severe acne rosacea [1]. In literature only 18 cases of giant rhinophyma are described [2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19] (Table 1).…”
Section: Introductionmentioning
confidence: 99%